PROGRESS IN THE STUDY OF DECAMETER-WAVELENGTH SOLAR RADIO EMISSION WITH UKRAINIAN RADIO TELESCOPES. Part 2. (Invited paper) - Stanislavsky, A. A.; Koval, A. A.; Bubnov, I. N.; Brazhenko, A. I. (Видавничий дім «Академперіодика», 2023)
Subject and Purpose. This part of the paper continues presentation of results of the solar radio emission studies performed with Ukrainian radio telescopes over the past 20 years. The importance is stressed of developing adequate instruments and methods for identifying the nature of decameter-wavelength radio emissions from the Sun.Methods and Methodology. The low frequency Ukrainian radio telescopes UTR-2, GURT and URAN-2 have been used in the project along with other ground- and space based instruments in order to achieve a comprehensive understanding of physical conditions in the solar corona.Results. Special methods and tools have been developed for studying radio frequency burst emissions against the background of strong interference. Unique data have been obtained concerning sources of sporadic radio emissions from the Sun, as well as the contribution from wave propagation effects and the impact of the ionosphere on the results of observations. The most significant observational and theoretical results are presented, obtained in the study of solar low frequency emissions over the past 20 years. Solar radio emissions are shown to be efficient sounding signals not for the solar corona alone but for the Earth’s ionosphere as well, which allows identifying its impact on the results of radio astronomy observations.Conclusions. The Ukrainian radio telescopes of the meter and decameter wavebands currently are unrivalled tools for investigating the Universe in the low-frequency range of radio waves. Owing to their advanced characteristics, they make a significant contribution to the progress of world’s solar radio astronomy.Keywords: the Sun, decameter-wavelength radio emission, radio bursts, solar corona, UTR-2, URAN-2, GURTManuscript submitted  02.06.2022Radio phys. radio astron. 2023, 28(3): 183-200REFERENCES    1. Volvach, Ya.S., Stanislavsky, A.A., Konovalenko, A.A., Koval, A.A., And Dorovsky, V.V., 2016. Comparative analysis of decametre "drift pair" bursts observed in 2002 and 2015. Adv. Astron. Space Phys., 6(1), pp. 24—27. DOI: https://doi.org/10.17721/2227-1481.6.24-27    2. Stanislavsky, A.A., Konovalenko, A.A., and Volvach, Ya.S., 2017. Frequency drift rate of solar decameter "drift pair" bursts. Res. Astron. Astrophys., 17(9), id. 097. DOI: https://doi.org/10.1088/1674-4527/17/9/97    3. Stanislavsky, A.A., Volvach, Ya.S., Konovalenko, A.A., and Koval, A.A., 2017. Solar drift-pair bursts. Sun Geosph., 12(2), pp. 99—103.    4. Stanislavsky, A.A., Konovalenko, A.A., Yerin, S.N., Bubnov, I.N., Zakharenko, V.V., Shkuratov, Yu.G., Tokarsky, P. L., Yatskiv, Ya.S., Brazhenko, A.I., Frantsuzenko, A.V., Dorovskyy, V.V., Rucker, H.O., and Zarka, P., 2018. Solar bursts as can be observed from the lunar farside with a single antenna at very low frequencies. Astron. Nachr., 339(7—8), pp. 559—570. DOI: https://doi.org/10.1002/asna.201813522    5. Stanislavsky, A.A., Bubnov, I.N., Konovalenko, A.A., Gridin, A.A., Shevchenko, V.V., Stanislavsky, L.A., Mukha, D.V., and Koval, A.A., 2014. First Radio astronomy examination of the low-frequency broadband active antenna subarray. Adv. Astron., 2014, id. 517058. DOI: https://doi.org/10.1155/2014/517058    6. Yerin, S., Stanislavsky, A., Bubnov, I., Konovalenko, A., Tokarsky, P., and Zakharenko, V., 2019. Small-sized radio telescopes for monitoring and studies of solar radio emission at meter and decameter wavelengths. Sun Geosph., 14(1), pp. 21—24. DOI: https://doi.org/10.31401/SunGeo.2019.01.03    7. Koval, A., Chen, Y., Stanislavsky, A., and Zhang, Q.-H., 2017. Traveling ionospheric disturbances as huge natural lenses: Solar radio emission focusing effect. J. Geophys. Res. Space Phys., 122(9), pp. 9092—9101. DOI: https://doi.org/10.1002/2017JA024080    8. Koval, A., Chen, Y., Stanislavsky, A., Kashcheyev, A., and Zhang, Q.-H., 2018. Simulation of focusing effect of traveling ionospheric disturbances on meter-decameter solar dynamic spectra. J. Geophys. Res. Space Phys., 123(11), pp. 8940—8950. DOI: https://doi.org/10.1029/2018JA025584    9. Koval, A., Chen, Y., Tsugawa, T., Otsuka, Y., Shinbori, A., Nishioka, M., Brazhenko, A., Stanislavsky, A., Konovalenko, A., Zhang, Q.-H., Monstein, Ch., and Gorgutsa, R., 2019. Direct observations of traveling ionospheric disturbances as focusers of solar radiation: Spectral caustics. Astrophys. J., 877(2), id. 98. DOI: https://doi.org/10.3847/1538-4357/ab1b52    10. Stanislavsky, A.A., Konovalenko, A.A., Rucker, H.O., Abranin, E.P., Kaiser, M.L., Dorovskyy, V.V., Mel’nik, V.N., and Lecacheux, A., 2009. Antenna performance analysis for decameter solar radio observations. Astron. Nachr., 330(7), pp. 691—697. DOI: https://doi.org/10.1002/asna.200911226    11. Konovalenko, A.A., Stanislavsky, A.A., Rucker, H.O., Lecacheux, A., Mann, G., Bougeret, J.-L., Kaiser, M.L., Briand, C., Zarka, P., Abranin, E.P., Dorovsky, V.V., Koval, A.A., Mel’nik, V.N., Mukha, D.V., and Panchenko, M., 2013. Synchronized observations by using the STEREO and the largest ground-based decametre radio telescope. Exp. Astron., 36(1—2), pp. 137—154. DOI: https://doi.org/10.1007/s10686-012-9326-x    12. Stanislavsky, A.A., Konovalenko, A.A., Zakharenko, V.V., Bubnov, I.N., Volvach, Ya.S., Dorovskyy, V.V., Koval, A.A., and Mylostna, K.Yu., 2016.Coordinated synchronous observations of Solar System objects using the ground- and space-based methods of low- frequency radio astronomy. Space Sci.&Technol., 21(4), pp. 51—55 (in Ukrainian). DOI: https://doi.org/10.15407/knit2015.04.051    13. Koval, A.A., Stanislavsky, A.A., Chen, Y., Feng, Sh., Konovalenko, A.A., and Volvach, Ya.S., 2016. A decameter stationary type IV burst in imaging observations on the 6th of September 2014. Astrophys. J., 826(2), id. 125. DOI: https://doi.org/10.3847/0004-637X/826/2/125    14. Stanislavsky, A.A., Konovalenko, A.A., Abranin, E.P., Dorovskyy, V.V., Lecacheux, A., Rucker, H.O., and Zarka, P., 2018. Revisiting the frequency drift rates of decameter type III solar bursts observed in July — August 2002. Sol. Phys., 293(11), id. 152. DOI:https://doi.org/10.1007/s11207-018-1374-6     15. Stanislavsky, A.A., Konovalenko, A.A., Koval, A.A., Dorovskyy, V.V., Zarka, P., and Rucker, H.O., 2015. Coronal magnetic field strength from decameter zebra-pattern observations: complementarity with band-splitting measurements of an associated type II burst. Sol. Phys., 290(1), pp. 205—218. DOI: https://doi.org/10.1007/s11207-014-0620-9    16. Stanislavsky, A.A., Koval, A.A., and Konovalenko, A.A., 2013. Low-frequency heliographic observations of the quiet Sun corona. Astronom. Nachr., 334(10), pp. 1086—1092. DOI: https://doi.org/10.1002/asna.201211839    17. Brazhenko, A.I., Koval, A.A., Konovalenko, A.A., Stanislavsky, A.A., Abranin, E.P., Dorovskyy, V.V., Melnik, V.M., Vashchishin, R.V., Frantsuzenko, A.V., and Borysyuk, O.V., 2012. Peculiarity of continuum emission from upper corona of the sun at decameter wavelengths. Radio Phys. Radio Astron., 3(3), pp. 187—196. DOI: https://doi.org/10.1615/RadioPhysicsRadioAstronomy.v3.i3.10    18. Konovalenko, O.O., Koshovyy, V.V., Lozynskyy, A.B., Stanislavsky, A.A., Shepelev, V.A., Ivantyshyn, O.L., Kharchenko, B.S., Lozynskyy, R.A., Brazhenko, A.I., Abranin, E.P., and Koval, A.A., 2012. Quiet Sun observations by URAN-2 and URAN-3 decameter radio telescopes during the solar eclipse of August 1, 2008. Radio Phys. Radio Astron., 17(4), pp. 295—300 (in Ukrainian).    19. Konovalenko, A.A., Stanislavsky, A.A., Abranin, E.P., Dorovsky, V.V., Mel’nik, V.N., Kaiser, M.L., Lecacheux, A., and Rucker, H.O., 2007. Absorption in Burst Emission. Sol. Phys., 245(2), pp. 345—354. DOI: https://doi.org/10.1007/s11207-007-9049-8    20. Stanislavsky, A.A., Bubnov, I.N., Koval, A.A., Yerin, S.N., 2022. Parker Solar Probe detects solar radio bursts related with a behind- the-limb active region. Astron. Astrophys., 657, A21. DOI: https://doi.org/10.1051/0004-6361/202141984    21. Stanislavsky, A.A., Burnecki, K., Magdziarz, M., Weron, A., and Weron, K., 2009. FARIMA Modeling of solar flare activity from empirical time series of soft X-ray solar emission. Astrophys. J., 693(2), pp. 1877—1882. DOI: https://doi.org/10.1088/0004-637X/693/2/1877    22. Stanislavsky, A.A., Burnecki, K., Janczura, J., Niczyj, K., and Weron, A., 2019. Solar X-ray variability in terms of a fractional heteroskedastic time series model. Mon. Not. R. Astron. Soc., 485(3), pp. 3970—3980. DOI: https://doi.org/10.1093/mnras/stz656    23. Stanislavsky, A., Nitka, W., Małek, M., Burnecki, K., and Janczura, J., 2020. Prediction performance of Hidden Markov modelling for solar flares. J. Atmos. Sol.-Terr. Phys., 208, id. 105407. DOI: https://doi.org/10.1016/j.jastp.2020.105407    24. Shkuratov, Y.G., Konovalenko, A.A., Zakharenko, V.V., Stanislavsky, A.A., Bannikova, E.Y., Kaydash, V.G., Stankevich, D.G., Korokhin, V.V., Vavriv, D.M., Galushko, V.G., Yerin, S.N., Bubnov, I.N., Tokarsky, P.L., Ulyanov, O.M., Stepkin, S.V., Lytvynenko, L.N., Yatskiv, Y.S., Videen, G., Zarka, P., and Rücker, H.O., 2018. Ukrainian mission to the Moon: how to and with what. Space Sci. Technol., 24(1), pp. 3—30 (in Ukrainian). DOI: https://doi.org/10.15407/knit2018.01.003    25. Shkuratov, Y.G., Konovalenko, A.A., Zakharenko, V.V., Stanislavsky, A.A., Bannikova, E.Y., Kaydash, V.G., Stankevich, D.G., Korokhin, V.V., Vavriv, D.M., Galushko, V.G., Yerin, S.N., Bubnov, I.N., Tokarsky, P.L., Ulyanov, O.M., Stepkin, S.V., Lytvynenko, L.N., Yatskiv, Y.S., Videen, G., Zarka, P., and Rücker, H.O., 2019. A twofold mission to the Moon: Objectives and payloads. Acta Astronaut., 154, pp. 214—226. DOI: https://doi.org/10.1016/j.actaastro.2018.03.038    26. Bubnov, I.N., Konovalenko, A.A., Tokarsky, P.L., Korolev, A.M., Yerin, S.N., and Stanislavsky, L.A., 2021. Creation and approbation of a low-frequency radio astronomy antenna for studying objects of the Universe from the far side of the Moon. Radio Phys. Radio Astron., 26(3), pp. 197—210 (in Ukrainian). DOI:https://doi.org/10.15407/rpra26.03.197    27. Stanislavsky, L.A., Bubnov, I.N., Konovalenko, A.A., Tokarsky, P.L., and Yerin, S.N., 2021. The first detection of the solar U+III association with an antenna prototype for the future lunar observatory. Res. Astron. Astrophys., 21(8), id. 187. DOI: https://doi.org/10.1088/1674-4527/21/8/187    28. Stanislavsky, A.A., Bubnov, I.N., Koval, A.A., Stanislavsky, L.A., Yerin, S.N., Zalizovski, A.V., Lisachenko, V.M., Konovalenko, O.O., Kalinichenko, M.M., 2023. Validation of F2-layer critical frequency variations in the ionosphere with radio observations of solar bursts. J. Atmos. Sol.-Terr. Phys., 245, id. 06056. DOI: https://doi.org/10.1016/j.jastp.2023.106056